Law Enforcement of the Crime of Human Trafficking against Indonesian Migrant Workers: An Analysis of Decision Number 1313/Pid.Sus/2023/PN Makassar - Mukhsin, Muh. Adit Anugrah; Razak, Askari; Badaru, Baharuddin (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study aims to analyze law enforcement against the crime of human trafficking involving Indonesian migrant workers, as well as the judicial considerations in Decision Number 1313/Pid.Sus/2023/PN Makassar. This research employs a normative legal method using statutory, case, and conceptual approaches. The results indicate that, from a juridical perspective, law enforcement against human trafficking has a strong legal foundation in both national law and international instruments. The court decision reflects the application of the principle of material truth and the independence of judicial power through juridical and sociological considerations. However, there remain weaknesses in the sentencing aspect, which has not fully produced a deterrent effect and has not optimally fulfilled victims’ rights, particularly concerning restitution and recovery approaches. This study recommends strengthening sentencing policies oriented toward substantive justice through the integration of retributive and restorative approaches, enhancing victim protection, and improving coordination and capacity of law enforcement authorities in order to increase the effectiveness of law enforcement and protection for Indonesian migrant workers